Flying to Paradise : The Role of Airlift in the Caribbean Tourism Industry - Acevedo Mejia, Sebastian (IMF Working Papers; Working Paper ;, 2016)
This paper studies the role of airlift supply on the tourism sector in the Caribbean. The paper examines the relative importance of U.S.-Caribbean airlift supply factors such as the number of flights, seats, airlines, and departure cities on U.S. tourist arrivals. The possible endogeneity problem between airlift supply and tourist arrivals is addressed by using a structural panel VAR and individual country VARs. Among the four airlift supply measures, increasing the number of flights is found to be the most effective way to boost tourist arrivals on a sustained basis. As a case study, the possible crowding effect of increasing the number of U.S. flights to Cuba is investigated and, based on past observations, we find no significant impact on flights to other Caribbean countries. The impact of natural disasters on airlift supply and tourist arrivals is also quantified.